Тhe value of transbronchial needle aspiration cytology in the diagnosis of stage I and II sarcoidosis - Tatomirović Željka; Škuletić Vesna; Peković Dragana; Karličić Vukoica; Đurović Branka; Ristić Saša; Tomić Ljiljana; Džambas Jelena; Cerović Snežana (Vojnosanitetski Pregled)
Background/Aim. Sarcoidosis is a multisystem infmammatory disease of unknown etiology, with the lungs and intrathoracic lymph nodes the most commonly involved. The aim of this study was to assess the contribution of conventional transbronchial needle aspiration (TBNA) cytology in the diagnosis of sarcoidosis presenting as mediastinal/hilar lymphadenopathy. Methods. In this retrospective study, 58 patients with suspicion of stage I and II sarcoidosis underwent first flexibile, and then, a rigid bronhoscopy, during which TBNA of mediastinal or hilar lumph node with a 19 gauge (G) needle was done. Material from the needle was put on glass slide and prepared for the cytological and histopathological examination. Results. Out of 58 patients submitted to TBNA of mediastinal or hilar lymph nodes, adequate material for cytological diagnostics was obtained in 53 (91.37%). Out of 53 adequate cytological samples, in 38 (71.69%) noncaseous granulomatous inflammation (NGI) was found, while in corresponding histopathological samples, NGI was found in 48 (90.56%), which was significantly higher (p < 0.05). Of cytological smears, out of the cell types typical for granulomatous inflammation, in 26 (63.15%) patients the clusters of the epitheloid cells were found, in 8 (21.05%) there were both, clusters of epitheloid cells and giant multinuclear hystiocytes, and in 6 (15.76%) only single scattered epitheloid cells or small clusters of several epitheloid cells were found. The sensitivity of TBNA cytology in our group of patients with sarcoidosis was 76%, specificity 100% and accuracy 77.34%. Conclusion. TBNA is an efficient and safe procedure in the diagnosis of sarcoidosis, minimally invasive and with a little risk of complications. Using 19 G needle enables obtaining material for histological and cytological analyses, as well which contribute to the sensitivity of diagnosting sarcoidosis. The value of this type of diagnostics depends on qualification and experience both of bronchoscopist and cytologist/pathologist, as well, of the interpreter of such a material.